The Bible in early transatlantic Pietism and Evangelicalism - Hoselton, Ryan P. 1987-; Stievermann, Jan 1975-; Sweeney, Douglas A. 1965-; Haykin, Michael A. G. 1953- (The Pennsylvania State University Press, 2022)
This collection of essays showcases the variety and complexity of early awakened Protestant biblical interpretation and practice while highlighting the many parallels, networks, and exchanges that connected the Pietist and evangelical traditions on both sides of the Atlantic.A yearning to obtain from the Word spiritual knowledge of God that was at once experiential and practical lay at the heart of the Pietist and evangelical quest for true religion, and it significantly shaped the courses and legacies of these movements. The myriad ways in which Pietists and evangelicals read, preached, translated, and practiced the Bible were inextricable from how they fashioned new forms of devotion, founded institutions, engaged the early Enlightenment, and made sense of their world. This volume provides breadth and texture to the role of Scripture in these related religious traditions. The contributors probe an assortment of primary source material from various confessional, linguistic, national, and regional traditions and feature well-known figures-including August Hermann Francke, Cotton Mather, and Jonathan Edwards-alongside lesser-known lay believers, women, people of color, and so-called radicals and separatists. Pioneering and collaborative, this volume contributes fresh insight into the history of the Bible and the entangled religious cultures of the eighteenth-century Atlantic world.Along with the editors, the contributors to this volume include Ruth Albrecht, Robert E. Brown, Crawford Gribben, Bruce Hindmarsh, Kenneth P. Minkema, Adriaan C. Neele, Benjamin M. Pietrenka, Isabel Rivers, Douglas H. Shantz, Peter Vogt, and Marilyn J. Westerkamp
Keywords: Geschichte 1650-1800; Bibellektüre; Evangelikale Bewegung; Pietismus; Biblizismus; Atlantischer Raum -- Nord; Evangelicalism / Europe / History / 18th century; Evangelicalism / North America / History / 18th century; Pietism / Europe / History / 18th century; Pietism / North America / History / 18th century; Bible / Criticism, interpretation, etc / History / 18th century; Bible / Commentaries / History and criticism